Seed inoculation of desert‐plant growth‐promoting rhizobacteria induce biochemical alterations and develop resistance against water stress in wheat. Issue 2 (18th February 2021) - Zia, Rabisa; Nawaz, Muhammad Shoib; Yousaf, Sumaira; Amin, Imran; Hakim, Sughra; Mirza, Muhammad Sajjad; Imran, Asma
Abstract: Water shortage limits agricultural productivity, so strategies to get higher yields in dry agricultural systems is vital to circumvent the effect of climate change and land‐shortage. The plant rhizosphere harbors beneficial bacteria able to confer biotic/abiotic tolerance along with a positive impact on plant growth. Herein, three bacterial strains, Proteus mirabilis R2, Pseudomonas balearica RF‐2 and Cronobacter sakazakii RF‐4 (accessions: LS975374, LS975373, LS975370, respectively) isolated from native desert‐weeds were investigated for their response to improve wheat growth under drought stress. The bacteria showed drought tolerance up to 20% polyethylene glycol (PEG; −0.6 MPa), and salt (65–97 g l −1 ), 1‐aminocyclopropane‐1‐carboxylate (ACC)‐deaminase activity, P/Zn/K‐solubilization, calcite degradation, IAA, and siderophore production. The plant growth‐promoting rhizobacteria (PGPR) were evaluated on wheat under water stress. The P. balearica strain RF‐2 primed seeds showed a maximum promptness index and germination index under PEG‐stress, that is, 68% and 100%, respectively. Inoculation significantly improved plant growth, leaf area, and biomass under water stress. P. mirabilis R2 inoculated plant leaves showed the highest water contents as compared to the plants inoculated with other strains. C. sakazakii RF‐4 inoculated plants showed minimum cell injury, electrolyte leakage, and maximum cell membrane stability at PEG stress. After 13 days exposure to drought, C. sakazakii RF‐4 treated plants showed an overall higher expression of cytosolic ascorbate peroxidase (cAPX) and ribulose‐bisphosphate carboxylase ( rbcL) genes. The activity of stress‐induced catalase and polyphenol oxidase was reduced, while that of peroxidase and superoxide dismutase increased after inoculation but the response was temporal. Taken together, this data explains that different PGPR (especially C. sakazakii RF‐4) modulate differential responses in wheat that eventually leads towards drought tolerance, hence, it has the potential to enhance crop production in arid regions.